Autonomous Surface Vehicle Controlling Menggunakan Kinect untuk Observasi Terumbu Karang - Khafiddurrohman Agustianto; Dyah Ayu Dwijayanti (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Autonomous Surface Vehicles (ASV) is a platform that is capable of recognizing oceanographic data that is moving on the surface of the sea. The ASV is commonly controlled using a remote RC, smartphones, joysticks, and keyboards. The development of control system innovations in the form of NUI, then ASV can be controlled using Kinect by someone without having to touch the remote. The study developed a marker-less ASV control using the Kinect skeleton feature to get the coordinate value to be the angle value of the right and left hand movement in the implemation as the value of the input fuzzy sugeno algorithm, which resulted in PWM speed output value. This marker-less development communicates wirelessly using the Xbee Pro S28 received by the Arduino Mega for communication and processing the running brushless motor and the ASV generates the movement according to the value received. Effect of light on Kinect in the efficient skeleton tracking process in the room maximum 53105 lux, and in the room maximum 201 lux. Object Spacing (Brainware) to read in the tracking process of the Kinect position of the efficient at a height of 120cm, and angle 00. Kinect communication distance with ASV reaches up to 10000cm. The success of a fuzzy calculation with the result of the movement of the ASV robot is 89.9%.